The Joint Effects of Multiple Legal System Characteristics on Auditing Standards and Auditor Behavior - Simunic, Dan A.; Ye, Minlei; Zhang, Ping (Contemporary Accounting Research, 2017)
Abstract This paper derives the impacts of legal system characteristics and auditing standards on auditor behavior (audit quality), and analyzes the determination of optimal auditing standards under different legal regimes. Legal regimes are characterized by differences in the uncertainty concerning the outcome of legal proceedings (termed vagueness of legal systems) and differences in the average size of damage awards. Auditing standards as determined by standard setters can vary in both toughness and vagueness. Our analysis provides implications for the adoption of International Standards on Auditing ( ISA ). Countries, such as the United States, where auditor legal liability is significantly more onerous than the global norm are not likely to adopt ISA , since these standards may not induce auditors to provide the optimal level of audit quality. Conversely, the adoption of ISA by countries, such as China, where the legal system makes the recovery of damages from auditors quite difficult, is not by itself likely to result in a high level of audit quality. Furthermore, our model suggests that auditor rotation can help improve audit quality, but only in certain circumstances.